(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Teenage is the time of shaping health behaviour and preventing postural defects and improving respiratory fitness. The teenagers possess insufficient knowledge about their respiratory system. Postural defects are commonly seen among teenagers due to lack of physical activity and poor postural habits which can lead to non harmonious development of organs and affect respiratory system as well. For efficient respiratory function, moderate intensity exercises with posture correction would be useful. There is paucity of literature showing effect of posture correction and moderate intensity exercises on respiratory system in teenagers, hence this study would be helpful to analyse the same. Objectives: To find out effect of posture correction exercise on respiratory system in teenagers. To find out effect of moderate intensity exercises on respiratory system in teenagers. Methodology: The study was carried out in karad area. The subjects were selected according to inclusion and exclusion criteria. Total 35 subjects were participated in this study. Prior consent and assent form was taken. Aim and procedure were explained to the subjects in their preferred language before data collection. Pre and post assessment was done by 6 minute walk test for respiratory function and flexicurve was measured using flexible ruler to recognize spinal postural defect. Peak flow meter was used to measure lung function Result: In conducted study, 6minute walk test, peak flow meter and flexicurve showed statistically significant difference between pre and post treatment values. Conclusion: On the basis of the result of the study, it can be concluded that posture correction and moderate intensity exercises helps in improving respiratory function in teenagers.